Compulsive Buying: An Exploration of Money Attitudes among Malaysian Consumers - Ong, Li Yin (2013)
Money is vital element of modern living and plays an important role in stimulating people and influences their buying decisions. Different individuals possesses different goals (e.g. enjoying life, acquiring power) besides accumulating wealth, and these goals will eventually lead to different dimensions of money attitudes which can be the motivators of compulsive buying. Indeed, most individuals regardless of their age, gender or social status can be expected to be the victim of impulsive buying. In Malaysia, this topic has been under-researched and the general idea of money attitudes was primarily focused on the western context. Thus, this study aims to investigate the relationship between money attitudes and compulsive purchase tendency in the Malaysian context. Based on the literature reviewed, a theoretical framework was developed and the researcher conducted a convenience sampling of data whereby 102 respondents were surveyed using questionnaires. The data was analyzed using the Statistical Package for Social Science (SPSS) version 20.0 and Partial Least Square (PLS) method. The results showed that individual’s money dimension of power/prestige and quality has an effect on their compulsive buying behavior. Specifically, the individuals’ money attitudes dimensions’ impact on compulsive buying behavior was strengthened in an indirect manner rather than direct. Thus, this research provides useful information to marketers and policy makers which will help them to better understand consumers’ spending behavior.